2011
DOI: 10.1111/j.1753-6405.2011.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Representations of childhood obesity in Australian newsprint media and academic literature

Abstract: IntroductionThe media can influence and shape public perception by choosing what and how to present information. 20,21 Highlighting some aspects of an issue and downplaying others contributes to how a particular issue is socially constructed.22,23 Furthermore issues that receive heavy coverage are often prioritised in public and policy agendas and the way they are framed can define public perceptions. 22,24 In Australia during February 2009 media attention focused on an academic report by medical professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…Fewer studies examined television (19)(20)(21), mixed broadcasting and print (22)(23)(24) or studied the content of online media sources (25). Obesity was explored predominantly in factual formats, specifically news stories (8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Regarding geographic focus, news reporting of obesity in the United States-based media outlets attracted most research attention (8,9,14,(22)(23)(24)28,29,(31)(32)(33)35,36), followed by media from Australia (11,15,16,18,19,…”
Section: Extant Research: Top-level Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies examined television (19)(20)(21), mixed broadcasting and print (22)(23)(24) or studied the content of online media sources (25). Obesity was explored predominantly in factual formats, specifically news stories (8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Regarding geographic focus, news reporting of obesity in the United States-based media outlets attracted most research attention (8,9,14,(22)(23)(24)28,29,(31)(32)(33)35,36), followed by media from Australia (11,15,16,18,19,…”
Section: Extant Research: Top-level Observationsmentioning
confidence: 99%
“…Countrycomparative approaches of obesity news representation were also scarce (34). Finally, the news representation of obesity was predominantly approached through the lens of framing theory and research (10)(11)(12)(13)(14)(15)(17)(18)(19)(20)(22)(23)(24)(25)(26)(27)(28)(29)(31)(32)(33)(34).…”
Section: Extant Research: Top-level Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bastian's analysis of both academic literature and Australian newspaper coverage of childhood obesity identified an emphasis on societal framings in the former, and individual framings in the latter. Lawrence's analysis of framing of obesity in US news articles and other texts found that, in the two decades preceding 2004, obesity frames shifted from individualised and medicalised conceptions to a greater focus on environmental causes.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on media representations of childhood obesity covers a broad range of focuses, including how media framing has defined obesity in terms of its causes and potential solutions , and the gendered nature of parental blame . Boero's review of social science perspectives on obesity media suggests that individual framings tend to dominate representations of obesity, but identifies childhood obesity as a possible exception, with blame for children's overweight shifted to parents and societal institutions.…”
Section: Introductionmentioning
confidence: 99%